A Prospective Study Of Cutaneous Manifestations Of Obesity (Journal of Pharmaceutical Negative Results, 2022)
BACKGROUND: In recent times obesity is considered a major health hazard with increasing prevalence. Age of onset of obesity, duration, and associated system conditions have a significant role in the cutaneous manifestations of obesity.METHOD:A prospective study was conducted for 1 year. Patients above 18 years and below 70 years of age attending dermatology OPD at a tertiary care center in Kanchipuram whose body mass index (BMI) >30 kg/m2 were included in the study.After taking informed consent, basic details of about 100 obese patients, past treatment history, height, and weight were noted. Detailed dermatological examination was done and the observations were recorded.RESULTS:The majority of the patients (72%) had Class I obesity (BMI of 30.00-34.99) while 19% had Class II obesity (BMI of 35.00-39.99), and 9% had Class III obesity (BMI of ≥ 40.00). Obesity was found to be more common in the female population.Acanthosis nigricans was the commonest cutaneous finding among all the age groups followed by skin tags. Infections were more common among the older age group whereas acne and hirsutism were more common among the younger age group.CONCLUSION: A lot of cutaneous manifestations have been associated with obesity ranging from infections to metabolic conditions. Identifying these manifestations at an early stage, promoting lifestyle modifications for weight reduction and aesthetic treatment for the skin condition helps in a better outcome.